Experimental and DFT Study on the Compounds [PdCl2L2] (L = 4-methylpyrazole, 4-iodopyrazole) - Barra, Carolina V. [UNESP]; Treu-Filho, Oswaldo [UNESP]; Rocha, Fillipe V. [UNESP]; Moura, Thales R. [UNESP]; Netto, Adelino V.G. [UNESP]; Mauro, Antonio E. [UNESP]; Pinheiro, José C.; Kondo, Rogério T. (Slovenian Chemical Society, 2015)
Theoretical molecular structures of the complexes [PdCl2(HmPz)2] (1) and [PdCl2(HIPz)2](2) (HmPz = 4-methylpyrazole; HIPz = 4-iodopyrazole) were studied using B3LYP/DFT method. The new complex 2 and the complex 1 were synthesized and characterized by elemental analysis and IR spectroscopy. The calculated bond distances and angles showed that both compounds exhibited a slightly distorted square planar coordination environment around the palladium center. The theoretical IR spectra of Cs symmetry (electronic state 1A') of the complexes agree well with the experimental data.
Keywords: DFT calculation; Infrared Spectroscopy; Palladium(II) complexes; Pyrazoles